(untitled) (International Conference on Modern Science and Scientific Studies, 2025)
In this article, the adoption of innovative technologies and teaching strategies has become essential for the advancement of higher education systems. One of the most notable developments in recent years is the credit-module system, which enables flexible learning opportunities for students. This article explores the impact of the credit-module system on promoting independent distance learning among students in non-philological disciplines. It highlights the necessity of establishing effective structures for self-directed learning and integrating modern educational technologies to enhance student engagement and academic success.